Bisphosphonates induce apoptosis in human breast cancer cell lines - Senaratne, S G (Nature Publishing Group, 2000)
Breast cancer has a prodigious capacity to metastasize to bone. In women with advanced breast cancer and bone metastases, bisphosphonates reduce the incidence of hypercalcaemia and skeletal morbidity. Recent clinical findings suggest that some bisphosphonates reduce the tumour burden in bone with a consequent increase in survival, raising the possibility that bisphosphonates may have a direct effect on breast cancer cells. We have investigated the in vitro effects of bisphosphonates zoledronate, pamidronate, clodronate and EB 1053 on growth, viability and induction of apoptosis in three human breast cancer cell lines (MDA-MB-231, Hs 578T and MCF-7). Cell growth was monitored by crystal violet dye assay, and cell viability was quantitated by MTS dye reduction. Induction of apoptosis was determined by identification of morphological features of apoptosis using time-lapse videomicroscopy, identifying morphological changes in nucleis using Hoechst staining, quantitation of DNA fragmentation, level of expression of bcl-2 and bax proteins and identification of the proteolytic cleavage of Poly (ADP)-ribose polymerase (PARP). All four bisphosphonates significantly reduced cell viability in all three cell lines. Zoledronate was the most potent bisphosphonate with IC(50)values of 15, 20 and 3 μM respectively in MDA-MB-231, MCF-7 and Hs 578T cells. Corresponding values for pamidronate were 40, 35 and 25 μM, whereas clodronate and EB 1053 were more than two orders of magnitude less potent. An increase in the proportion of cells having morphological features characteristic of apoptosis, characteristic apoptotic changes in the nucleus, time-dependent increase in the percentage of fragmented chromosomal DNA, down-regulation in bcl-2 protein and proteolytic cleavage of PARP, all indicate that bisphosphonates have direct anti-tumour effects on human breast cancer cells. © 2000 Cancer Research Campaign